Parenting, Socioeconomic Status Risk, and Later Young Adult Health: Exploration of Opposing Indirect Effects via DNA Methylation. Issue 1 (28th January 2016) - Beach, Steven R. H.; Lei, Man‐Kit; Brody, Gene H.; Kim, Sangjin; Barton, Allen W.; Dogan, Meesha V.; Philibert, Robert A.
Abstract : A sample of 398 African American youth, residing in rural counties with high poverty and unemployment, were followed from ages 11 to 19. Protective parenting was associated with better health, whereas elevated socioeconomic status (SES) risk was associated with poorer health at age 19. Genome‐wide epigenetic variation assessed in young adulthood (age 19), was associated with both SES risk and protective parenting. Three categories of genes were identified whose methylation was associated with parenting, SES risk, and young adult health. Methylation was a significant mediator of the impact of parenting and SES risk on young adult health. Variation in mononuclear white blood cell types was also examined and controlled, showing that it did not account for observed effects of parenting and SES risk on health.